Efforts To Overcome Training Burnout Among Badminton Athletes: A Quantitative Analysis - Muhammad Rizky Putra Hadi; Rahmadi; Abd. Hamid (Physical Education Departement of University PGRI Jombang, 2024)
This study aims to examine the efforts to address training burnout among badminton athletes at PB Berkat Abadi in Banjar Regency. Utilizing a descriptive quantitative approach with a survey method, this research analyzes the intrinsic and extrinsic factors contributing to the efforts to overcome training burnout among badminton athletes. The study involved 38 athletes, selected through total sampling. Data collection was conducted using a questionnaire adapted from previous research on levels of effort to overcome training burnout, assessing various indicators including determination, awareness, discipline, psychological aspects, variation, communication, facilities, rewards, and individual training planning. The results reveal that intrinsic factors contribute 45% to the overcoming burnout efforts, with psychological/mental aspects showing the highest individual contribution (11.48%), followed by determination and inner strength (15.39%), discipline (9.09%), and awareness of the importance of training (9.04%). Extrinsic factors account for 39.02% of the total effort, with the highest contribution from facilities and infrastructure (9.21%), followed by training variation (8.48%), individual-based training planning (8.27%), rewards (7.24%), and communication (5.82%). All indicators were categorized as